Dexamethasone for preventing postoperative nausea and vomiting in hysterectomized patients - Roberto González Castilla; Caridad Chacón Docassal; Yakelin Favier Tamayo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Dexamethasone, long-acting corticosteroid, is a drug whose characteristics favor its use in the treatment of nausea and vomiting in certain circumstances, however, its usefulness to prevent postoperative nausea and vomiting in patients undergoing neuroaxial intrathecal anesthesia, performed an abdominal hysterectomy, is not determined. Objective: to demonstrate the effectiveness of dexamethasone in the prevention of postoperative nausea and vomiting in hysterectomized patients under intraaxial neuraxial anesthesia. Methods: a descriptive and prospective study was conducted in patients who underwent hysterectomy under regional intraaxial neuraxial anesthesia (N = 50), from December 2012 to February 2013, at the Ambrosio Grillo Hospital in Santiago de Cuba. Two groups of similar number of patients, randomly selected were used: one treated conventionally (diazepam and diphenhydramine), and another group which was also administered dexamethasone. Results: in general, 8 patients (32%) presented postoperative nausea, 8 from the group treated with the usual form, and 6 treated dexamethasone (24%). Conclusion: the use of dexamethasone in hysterectomized patients under intrathecal neuraxial anesthesia decreases the total incidence of postoperative nausea and vomiting, though not significantly.